Molecular identification of strains of Bacillus spp. and its use as growth-promoting rhizobacteria in tomato (Lycopersicum esculentum Mill.) (Scientia Agropecuaria, 2020)
The application of plant growth promoting rhizobacteria (PGPR) constitutes an ecological practice that contributes to agricultural production systems and is presented as an option for reducing the use of chemical fertilizers. The tomato is in high demand around the world, its production requires efficient nutrition to supply the quantity and quality demand that the market requires, therefore, in the present investigation two bacterial strains were evaluated: Bacillus licheniformis (IB10) and Bacillus megaterium (CT11) as growth promoters in kidney tomato seedlings by testing in seedbeds. Statistical differences are evident in the different variables evaluated, the application of specific B. licheniformis at the time of planting caused an increase of 10% in the thickness of the stem and a 100% increase in the amount of dry biomass, the weekly application of B. megaterium problems the photosynthetic efficiency in 18% and problems in 11% the length of the roots of the seedlings. The results generated may allow the bacterial strains to be used as alternatives to chemical fertilizers.
Keywords: Plant growth promoting rhizobacteria; Bacillus; rhizobacteria; biofertilizer; promoter.